Access to health insurance amongst people with disabilities and its association with healthcare use, health status and financial protection in low- and middle-income countries: a systematic review - Luthfi Azizatunnisa’; Hannah Kuper; Lena Morgon Banks (International Journal for Equity in Health)
Abstract Background People with disabilities often incur higher costs for healthcare, due to higher needs, greater indirect costs, and the need for services not offered by the public system. Yet, people with disabilities are more likely to experience poverty and so have reduced capacity to pay. Health insurance is an important social protection strategy to meet healthcare needs and avoid catastrophic expenditures for this group. This systematic review synthesized evidence on health insurance coverage and potential effects among people with disabilities in low- and middle-income countries (LMICs). Methods This systematic review followed PRISMA Guidelines. We searched English peer-reviewed articles from nine databases (Medline, Embase, CINAHL, Web of Science, Scopus, Cochrane Library, PsyInfo, Global Health, and Econlit) from January 2000 to 24 January 2023. Two independent reviewers conducted the article selection, data extraction, and risk of bias assessment using NIH Guidelines. Studies were eligible for inclusion if they quantitatively assessed at least one of four key outcomes amongst people with disabilities: health insurance coverage/access, the association between health insurance and health care utilization, financial protection, or health status/outcome. Narrative synthesis was deployed due to high variety of outcome measurements. Results Out of 8,545 records retrieved and three from hand search, 38 studies covering data from 51 countries met the eligibility criteria. Over two-thirds (68.4%) focused on access/coverage, which was generally limited amongst people with disabilities. Seventeen studies (44.7%) examined healthcare utilization, with a positive association (9/12) found between health insurance and the use of disability-related services. However, its association with general healthcare utilization (5 studies) remained inconclusive. Financial protection, explored by six studies (15.8%), similarly yielded inconclusive results. Only four studies (10.5%) reported on health status, and the findings suggest a favourable association of health insurance with self-reported health among people with disabilities (2/4), despite the limited number of high-quality studies. Conclusions There is considerable variability and limited evidence regarding health insurance coverage and its potential impact among individuals with disabilities in LMICs. This gap highlights the pressing need for further evaluations of health insurance, with a specific focus on people with disabilities, aligning with the broader goal of achieving Universal Health Coverage (UHC). Trial registration PROSPERO CRD42023389533.